Core Outcome Measures for Perioperative and Anaesthetic Care (COMPAC): a modified Delphi process to develop a core outcome set for trials in perioperative care and anaesthesia. (January 2022) - Boney, Oliver; Moonesinghe, S. Ramani; Myles, Paul S.; Grocott, Michael P.W.; ,; Bartoszko, J.; Beattie, W.S.; Bellomo, R.; Buggy, D.; Cabrini, L.; Canet, J.; Cook, T.; et al.
Abstract: Background: Outcome selection underpins clinical trial interpretation. Inconsistency in outcome selection and reporting hinders comparison of different trials' results, reducing the utility of research findings. Methods: We conducted an iterative consensus process to develop a set of Core Outcome Measures for Perioperative and Anaesthetic Care (COMPAC), following the established Core Outcome Measures for Effectiveness Trials (COMET) methodology. First, we undertook a systematic review of RCTs in high-impact journals to describe current outcome reporting trends. We then surveyed patients, carers, researchers, and perioperative clinicians about important outcomes after surgery. Finally, a purposive stakeholder sample participated in a modified Delphi process to develop a core outcome set for perioperative and anaesthesia trials. Results: Our systematic review revealed widespread inconsistency in outcome reporting, with variable or absent definitions, levels of detail, and temporal criteria. In the survey, almost all patients, carers, and clinicians rated clinical outcome measures critically important, but clinicians rated patient-centred outcomes less highly than patients and carers. The final core outcome set was: (i) mortality/survival (postoperative mortality, long-term survival); (ii) perioperative complications (major postoperative complications/adverse events; complications/adverse events causing permanent harm); (iii) resource use (length of hospital stay, unplanned readmission within 30 days); (iv) short-term recovery (discharge destination, level of dependence, or both); and (v) longer-term recovery (overall health-related quality of life). Conclusions: This core set, incorporating important outcomes for both clinicians and patients, should guide outcome selection in future perioperative medicine or anaesthesia trials. Mapping these alongside standardised endpoint definitions will yield a comprehensive perioperative outcome framework.